Susceptibility of anurans, lizards, and fish to infection with Dracunculus species larvae and implications for their roles as paratenic hosts - Erin K. Box (Nature Portfolio, 2021)
Abstract Dracunculus spp. are parasitic nematodes that infect numerous species of mammals and reptiles. The life cycles of Dracunculus species are complex, and unknowns remain regarding the role of paratenic and transport hosts in transmission to definitive hosts. We had two primary objectives: to assess the susceptibility of several species of anurans, lizards, and fish as paratenic hosts for Dracunculus species, and to determine the long-term persistence of Dracunculus infections in African clawed frogs (Xenopus laevis). Animals were orally exposed to copepods infected with infectious third-stage larvae (L3s) of either Dracunculus insignis or D. medinensis. Dracunculus L3s were recovered from four anuran species, two lizard species, and one fish species, demonstrating that Dracunculus can infect tissues of a diversity of species. In long-term persistence trials, D. medinensis L3s were recovered from African clawed frogs tissues up to 58 days post-infection, and D. insignis L3s were recovered up to 244 days post-infection. Our findings regarding the susceptibility of novel species of frogs, lizards, and fish to infection with Dracunculus nematodes, and long-term persistence of L3s in paratenic hosts, address pressing knowledge gaps regarding Dracunculus infection in paratenic hosts and may guide future research regarding the transmission of Dracunculus to definitive mammalian hosts.